A Legal Analysis of the Extension of the Mandatory Retirement Age for Notaries Following Constitutional Court Decision No. 84/PUU-XXII/2024: Analisis Hukum Perpanjangan Usia Pensiun Wajib bagi Notaris Pasca Putusan Mahkamah Konstitusi Nomor 84/PUU-XXII/2024 - Rachael Shellofariq Darmawan; Denise Elysia Louise (Academia Open, 2025)
General Background: The regulation of notaries’ retirement age in Indonesia has long been debated for its incompatibility with contemporary professional dynamics and increased life expectancy. Specific Background: Constitutional Court Decision No. 84/PUU-XXII/2024 redefines eligibility for notarial tenure by shifting emphasis from age-based to competency-based assessment. Knowledge Gap: However, the legal implications of this paradigm shift and its impact on professional governance remain insufficiently examined. Aims: This study analyzes the relevance and juridical consequences of the Court’s decision for reformulating Indonesia’s maximum notarial retirement age. Results: Using a normative juridical approach, the findings show that the decision provides a constitutional foundation for extending tenure based on competence, health, and integrity while urging clearer and more objective implementing regulations to reduce legal uncertainty and administrative discrimination. Novelty: The study demonstrates that extending retirement age up to 70 years can strengthen service continuity and the quality of authentic deeds when supported by periodic professional evaluations. Implications: These insights position the Court’s decision as critical momentum for modernizing Indonesia’s notarial system toward more adaptive, equitable, and quality-oriented professional governance. Highlights: The Constitutional Court shifts retirement eligibility from age-based rules to competence-based assessment. Extending the notary retirement age to 70 enhances service continuity and maintains deed quality. Clear, objective implementing regulations are essential to prevent legal uncertainty and discrimination. Keywords: Notary, Retirement Age, Constitutional Court, Professional Competence, Legal Certainty